THE PLACE OF THE DIGITAL ECONOMY IN YOUTH EDUCATION (Academia Science Repository, 2023)
In the current process of rapid globalization, the role of the digital economy in determining the economy and competitiveness of the countries of the world is of great importance. No matter which industry or sector of the economy we look at, we see the place of digital technologies in all of them. President Shavkat Mirziyoyev, in his address to the parliament this year, paid special attention to the fact that in order to achieve progress, it is necessary and necessary for us to acquire digital knowledge and modern information technologies, which will give us the opportunity to take the shortest path to progress, because today information technologies are deeply penetrating all areas of the world. First of all, let's briefly answer the question why the digital economy is important for human development.